Developing modern database applications with PostgreSQL : use the highly available object-relational database to build scalable and reliable PostgreSQL apps /: use the highly available object-relational database to build scalable and reliable PostgreSQL apps. (2021) - Le, Quan Ha; Díaz, Marcelo
No abstract available